Pharmacological Versus Non-Pharmacological and Ancillary Mechanisms in Eye Drops Used in the Treatment of Glaucoma - Nicoletta Marchesi; Foroogh Fahmideh; Annalisa Barbieri; Marco Racchi; Alessia Pascale; Stefano Govoni (Frontiers Media S.A., 2022)
Medical Devices Made of Substances (MDMS) are increasingly used in the healthcare system alongside classic medicinal products and constitute an important field of experimentation and innovation in the biomedical field. In fact, these products are rapidly establishing themselves as a valuable therapeutic resource and are available in various forms including, but not limited to, creams, syrups, nasal or oropharyngeal sprays, and eye drops. MDMS are marketed to treat different diseases and the advantages and benefits of the use of these products can be claimed, once proven their clinical activity. What are the differences between medicinal products and MDMS? The substantial difference lies in the mechanism of action: the first case is based on pharmacological, metabolic, and immunological actions while the second one is based on mechanical, or chemical/physical action. Sometimes the boundaries are not well defined and there is a need for a reassessment and a consensus on the underlying concepts and definitions, also in the light of the increasing ability to recognize molecular mechanisms underneath the action of several substances not acting through an easy recognizable unique target (as a receptor, for example). In the present paper, we discuss the role of eye drops as an example of MDMS used in glaucoma, a widely diffused eye disease. The choice is due to the fact that some products used in this field of application and containing similar substances are marketed either as medicinal products or as medical devices or, using other dosage forms, as food supplements. Accordingly, it is important to underscore in the various cases what may be the principal mode of action and the contribution of additional mechanisms as derived, for example, from system pharmacology data. Their analysis may help to exemplify some of the problems around the sometimes fuzzy border between MDMS and medicinal products suggesting the need for new definitions and regulatory decisions about MDMS.